INDIGENOUS KNOWLEDGE, SOCIAL RELATIONSHIPS AND HEALTH: COMMUNITY-BASED PARTICIPATORY RESEARCH WITH ANISHINABE YOUTH AT PIC RIVER FIRST NATION - Big-Canoe, Katie (Scholarship@Western, 2011)
Canada’s First Nations youth endure a disproportionate burden of health inequalities. While patterns of First Nation’s youth health point to distinctly social causes (e.g., lacking social support, violence and addiction), research has not adequately explored how the quality of local social environments influence First Nations youth health. Drawing from 19 in-depth interviews with Anishinabe youth, this community-based project utilized an Indigenous Knowledge framework to explore youth perceptions of health, social relationships, and the ways they interact. This research centred around four main objectives including: 1) understanding how Anishinabe youth define health & well-being; 2) exploring youth perceptions of social relationships; 3) examining how social relationships influence health; and, 4) understanding how culture shapes health. Findings suggest that youth definitions of health differ across individual, family and community levels. Youth perceive social relationships as fundamental for the provision of social support, and that good relationships influence healthy behaviours (e.g. youth participation in ceremonies). Over time, it appears that loss of Indigenous Knowledge figures strongly in the declining relationship between health and social relationships of youth (e.g. changing ways of interacting). Despite the loss of knowledge and changing lifestyles of the community however, youth spoke about meaningful connections to the land, and they identified the importance of cultural teachings related to Indigenous knowledge (e.g., moral values such as respect for land/elders) in their everyday lives, social relationships, and health behaviours.